Effect of Ridge Width on the Lasing Characteristics of Triangular and Rectangular InAs/In0.53Ga0.47As Quantum Well Lasers - Jiao, Zhejing; Gu, Yi; Zhang, Yonggang; Hu, Anduo; Gong, Qian; Wang, Shumin; Li, Tao; Li, Xue (Frontiers in Materials, 2022)
The lasing characteristics of InP-based InAs/In0.53Ga0.47As quantum well (QW) lasers with different ridge widths are investigated. Two groups of lasers are grown for comparison, one with active triangular QW regions and the other with rectangular QW regions. Their output powers, characteristic temperatures (T0), external differential quantum efficiencies (ηd) and junction temperatures (Tj) are analyzed and compared. The parameter of ridge width is found to play an important role in the performance of the lasers. In triangular QW lasers, by broadening the ridge width from 8 to 12 μm, output power and ηd of the lasers are decreased for the temperature range of 100 to 320 K due to heating effect. But by broadening the ridge width from 8 to 100 μm in rectangular QW lasers, output power has about 3.5 time increase at 100 K and ηd also has a little increase for temperatures from 100 to 180 K due to much larger emission area and much faster heat dissipation. Tj, the real temperature of the active region, is also found to have accelerated increase at high injection current and heat sink temperature. Besides, compared to the rectangular QW laser of the same ridge width, the improved thermal performance of triangular QW laser is also demonstrated.